Ultrasound-guided vs. Non-ultrasound-guided femoral artery puncture techniques: a comprehensive systematic review and meta-analysis - Yi-Chen Huang; Yueh-Hsun Lu; Wei-Yi Ting (The Ultrasound Journal)
Abstract Purpose To compare the effectiveness of ultrasound-guided (US) versus non-US femoral artery puncture (FAP) methods, including fluoroscopy-guided (FL) and non-guided (NG) techniques. Materials This meta-analysis included 11 randomized controlled trials and 1 non-randomized retrospective study, comprising a total of 12 studies involving 5534 patients across diverse clinical settings. Studies varied in operator experience, institutional settings, and procedural protocols. Key outcomes assessed included complication rates, vessel access time, first-pass success rates, number of attempts, and the risk of accidental venipuncture. Results Analysis of the heterogeneous dataset showed that guided techniques were associated with reduced complication rates compared to NG methods (pooled odds ratio (OR): 0.45, 95% Confidence Interval (CI) 0.28–0.73). US guidance was associated with decreased vessel access time (mean difference: − 16.30 s, 95% CI − 29.83 to − 2.76), higher first-pass success rates (pooled OR: 3.54, 95% CI 2.36 to 5.30), and required fewer attempts compared to non-US techniques. US guidance also showed lower risk of inadvertent venipuncture (pooled OR: 0.22, 95% CI 0.14 to 0.34). Conclusion This meta-analysis suggests potential benefits of US femoral artery puncture techniques over non-US methods, while acknowledging significant heterogeneity across studies. The observed advantages in procedural outcomes varied across different clinical settings and operator experience levels. These findings provide setting for institutional decision-making regarding the implementation of guided puncture methods, considering factors such as operator expertise, resource availability, and specific patient populations.